2018
DOI: 10.3389/fimmu.2018.01605
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Roles of Mitochondria in Immune Responses: Novel Insights Into Immuno-Metabolism

Abstract: Lack of immune system cells or impairment in differentiation of immune cells is the basis for many chronic diseases. Metabolic changes could be the root cause for this immune cell impairment. These changes could be a result of altered transcription, cytokine production from surrounding cells, and changes in metabolic pathways. Immunity and mitochondria are interlinked with each other. An important feature of mitochondria is it can regulate activation, differentiation, and survival of immune cells. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
275
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(289 citation statements)
references
References 151 publications
(163 reference statements)
10
275
0
4
Order By: Relevance
“…Mitochondria regulate energy production through the coordination of fission (fragmentation of mitochondria) and fusion (elongation of mitochondria). Fused mitochondrial morphology supports higher levels of ATP generation via oxidative phosphorylation (Angajala et al, 2018). Fusion and fission is a dynamic process regulated by a number of proteins.…”
Section: Post-transcriptional Circadian Regulation Influences Atp Promentioning
confidence: 97%
“…Mitochondria regulate energy production through the coordination of fission (fragmentation of mitochondria) and fusion (elongation of mitochondria). Fused mitochondrial morphology supports higher levels of ATP generation via oxidative phosphorylation (Angajala et al, 2018). Fusion and fission is a dynamic process regulated by a number of proteins.…”
Section: Post-transcriptional Circadian Regulation Influences Atp Promentioning
confidence: 97%
“…Malfunction of mitochondrial processes implicated specifically in AD include oxidative damage (Nunomura et al, 2001) and accumulation of APP on mitochondrial membranes (Anandatheerthavarada et al, 2003). More recently it has been shown that mitochondria are important in immune cell regulation; influencing immune cell metabolism, differentiation, activation of the inflammatory response and regulating transcription (Angajala et al, 2018). Variants in mitochondrial DNA (mtDNA) have been associated with AD (Shoffner et al, 1993), but many of the processes that affect mitochondrial function, involve nuclear-encoded proteins (Ali et al, 2019), so it is more likely that variants in nuclear genes that affect mitochondrial function will affect AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we set to determine the cell intrinsic stimuli (DAMPs) that fuels the enduring IFNs signaling in Irgm1 -/mice. In the absence of external stimuli, the endogenous DAMPs from dysfunctional mitochondria are the major triggers for the type 1 IFN response (Angajala et al, 2018;West et al, 2015;Zhang et al, 2010). We and others have shown that depletion of IRGM in human cells or mice results in defective autophagy (Dong et al, 2015;He et al, 2012;Mehto et al, 2019) ( Supplementary Figure 5A and 5B) and this can result in impaired mitophagy and accumulation of defunct mitochondria.…”
Section: Irgm Mediates P62-dependent Autophagic Degradation Of Nucleimentioning
confidence: 91%
“…This data is consistent with previous observations where overexpression of IRGM leads to mitochondrial fission and depolarization (Singh et al, 2010), and here we observed fused and hyperpolarized mitochondria in IRGM deficient cells. The hyperpolarized state of mitochondria is often associated with the production of mitochondrial reactive oxygen species (mtROS) leading to apoptosis or necrosis and also autoimmune diseases (Angajala et al, 2018;Chen et al, 2017;Galloway and Yoon, 2012;Gergely et al, 2002a;Gergely et al, 2002b;Perl et al, 2004). Indeed, the mitochondrial superoxide and cellular total ROS levels, as measured by MitoSOX™ and CellRox™ dyes, were elevated in IRGM-depleted THP-1 cells, mice BMDM's and human PBMC's ( Figure 5P, Supplementary figure 5G and 5H).…”
Section: Irgm Mediates P62-dependent Autophagic Degradation Of Nucleimentioning
confidence: 98%